Etiologic and epidemiologic study of hepatocellular carcinoma in West Azarbaijan of Iran (2006-2011) - Nasim Valizadeh; Rahim Mehdioghli; Ramin Behroozian (Indian Journal of Medical and Paediatric Oncology)
Background: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide. Epidemiologic and etiologic studies help in the prevention of disease and improve surveillance of affected patients. The aim of this study was to study the etiology and epidemiology of HCC in West Azarbaijan of Iran. Materials and Methods: In this cross-sectional, retrospective study, medical records of 60 patients with HCC who were diagnosed between 2006 and 2011 in West Azarbaijan of Iran were analyzed for age, sex, location, presence of liver cirrhosis and/or well-known risk factors of HCC. Data were analyzed by SPSS 17 software. Results: From 60 patients with HCC, 75% were male and 25% were female. Mean age of the patients was 63.47 years. 51.66% were from rural areas and 48.33% were from urban areas. 43.33% of HCC patients were cirrhotic while 56.66% patients were non-cirrhotic. Of the 26 cirrhotic patients, 57.69% were seropositive for hepatitis B surface antigen (HBsAg), 15.38% not only had history of excess alcohol intake but were also HBsAg positive, 3.84% had history of alcoholism, 3.84% had history of Wilson disease and the rest (19.24%) had cryptogenic cirrhosis. Of the 34 non-cirrhotic patients, 35.29% were positive for HBsAg. None of the 60 patients with HCC had positive serology for hepatitis C virus (HCV) or history of hepatitis C infection. Conclusion: In our study, most of the patients (>50%) with HCC did not have underlying liver cirrhosis. In the cirrhotic patients, hepatitis B infection was the most common predisposing factor, followed by hepatitis B infection concomitant with alcoholism, alcoholism alone and Wilson disease. In the remaining cirrhotic patients, we could not find any predisposing factor for cirrhosis. Infection with HCV was not found in our studied group. We concluded that etiology of HCC in our province is different from that in the western countries.